Temps, progrès et races dans les Lumières écossaises - Silvia Sebastiani (Cahiers d’histoire.)
Recent historiography has identified an important point : Scotland’s Enlightenment literati – David Hume, Adam Smith, Adam Ferguson, Lord Kames, William Robertson, and John Millar – contributed to establish a new historical method based on the idea of progress. My aim here is to show that ‘race’ was one of the answers that the Scots gave to the questions opened up by a progressive conception of history. Scottish literati explained the observable differences among peoples according to a universal pattern of development, from ‘savagery’ to ‘civil society’. The comparative perspective enabled the ‘savage’ and the ‘civil’ to be examined as subjects of societies on the same historical path, though progressing along it at different rates and in different times. Although this historical method meant that the ‘savage’ could become ‘civil’ by means of progress, the very principle of comparison raised two other problems : first, the problem of the social and cultural distance between different societies; second, the question of the unequal progress. Why had Amerindians remained in the ‘savage’ stage of hunting ? Why were the societies of Northern Europe considered the only ones to have completed all the stages of historic progress ? In seeking to explain the crucial question of non-homogeneous progress of human societies, Scotland’s Enlightenment literati deployed an analysis that came to rely on the concept of ‘race’.